1999
DOI: 10.1080/14634989908656939
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the alterations of the aquatic environment downstream from a polluted tributary of the river Po (Italy)

Abstract: A comprehensive evaluation of the results of many recent and ongoing studies has been performed in an attempt to assess which stressors are acting and what alterations could be derived for the aquatic organisms of the river Po downstream from one of its tributaries, the river Lambro. With this aim in view, this stretch of the river Po was compared with the immediate upper reach which is characterized by an overall good quality. The comparison was based on four categories of indicators, that is, watershed stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The Lambro River is a tributary of the Po River, the principal Italian water course, that drains a heavily industrialized and densely inhabited subbasin of the main river. Previous studies have demonstrated that the Po River and its affluent collect compounds1‐3 that can act as endocrine disrupters (EDs) in fish population 4. The aims of the first year of this specific project task were to characterize the Po River fish community in two selected stretches (upstream and downstream of the Lambro River confluence); to analyze gonad morphology, vitellogenin, and sex steroid hormone plasma levels in fish captured upstream and downstream; and to select sentinel species to be used in the wild and in lab studies.…”
Section: Introductionmentioning
confidence: 99%
“…The Lambro River is a tributary of the Po River, the principal Italian water course, that drains a heavily industrialized and densely inhabited subbasin of the main river. Previous studies have demonstrated that the Po River and its affluent collect compounds1‐3 that can act as endocrine disrupters (EDs) in fish population 4. The aims of the first year of this specific project task were to characterize the Po River fish community in two selected stretches (upstream and downstream of the Lambro River confluence); to analyze gonad morphology, vitellogenin, and sex steroid hormone plasma levels in fish captured upstream and downstream; and to select sentinel species to be used in the wild and in lab studies.…”
Section: Introductionmentioning
confidence: 99%
“…The latter (with a watershed of about 3000 km 2 ) contributes about 50% of the total Cd load generated in the entire river Po basin; 40% of Pb; 20% of Cu and Zn; and 10% of As, Cr, and Ni (25). Biological effects of anthropogenic contamination in the Lambro-Po system include chronic (and occasionally acute) toxicity, as determined in laboratory tests, and reduced biodiversity in the field (26,27).…”
Section: Methodsmentioning
confidence: 99%